CONTRIBUTION TO GEOLOGY AND GENETIC PATHWAY OF THE ROPOČEVO BRECCIA – AN "ORPHAN" OLISTOLITHIC BODY WITHIN THE UPPER CRETACEOUS FLYSCH NEAR SOPOT (CENTRAL SERBIA) (Geologica Macedonica, 2022)
The Ropočevo breccia, a dimension stone highly prized in 20th century, has been examined by numerous prominent geologists of the time. It is revisited by researchers still intrigued by its perplexing provenance. Its position as a rigid exotic block of hard and completely metamorphosed carbonate breccia within the moderately lithified Upper Cretaceous flysch sequence remains unsolved due to absence of its source. Large bodies of a monomictic breccia suggest a relatively monotonous protolith carbonate sequence of significant thickness, such as those being formed in a calm marine environment with gradually sinking bottom due to epeirogenic movements. Varicoloured laminations indicate slight variations in the feeding material due to the epeirogenic oscillation of the basin bottom level. There is no regularity in clast distribution regarding size, colour or roundedness degree. This, paired with the occurrence of the "in-place brecciation" suggests a sudden fall of brecciated material due to a "catastrophic" event, such as earth-quake, collapse brecciation due to karst dissolution and a large sinkhole formation, or a graben/trench formation as in onset of the extensional processes.
Keywords: marble breccia; olistolith; Upper Cretaceous flysch